PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Pada Pelanggan Moment Coffeeshop Semarang) - Reza Adi Prabowo, 15.05.51.0007; Tjahjaningsih, Endang (Students' Journal of Economic and Management, 2019)
This study aims to examine and analyze the effect of product quality, price perception, and service quality on customer satisfaction at the Semarang Moment Coffeeshop. The population in this study are customers who buy products at the Semarang Coffeeshop Moment, because the population is very large, this study takes a sample of 100 respondents. The sampling technique in this study uses purposive sampling, namely the technique of determining samples with certain criteria, namely people who use boarding house services in Sampangan The data used in this study is primary data, with a questionnaire as a research instrument. The analytical tool used is multiple linear regression, validity test, reliability test, F test, coefficient of determination test (R²), and t test, which is then processed by calculation of SPSS (Statistical Product and Solutions) version 19. The results showed that product quality has a positive and significant effect on customer satisfaction, the perception of price prices has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction.